Processing of Ready-to-Brewed Drink from Pomelo, Baby Orange, and Lemon Peel Combination - Angger Mas Rizki Kusuma; Iffah Muflihati; Sari Suhendriani; Alpin Hidayatulloh (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2022)
Indonesia has a high potential for the production and consumption of oranges. Orange peel is a fruit waste that has the potential to be processed into food products, one of which is ready-to-brewed drinks. Ready-to-brewed drinks are one of the drinks that are easy to find, popular and popular in Indonesia. This study aims to determine the chemical and sensory characteristics of ready-to-drink drinks from the combination of orange peels of various varieties such as pomelo, baby orange, and lemon. The product is made through skin separation, cutting, blanching, immersion in ice water, and drying. The results showed that the water content of orange peel tea was following the SNI standard, which was below 8.00%. Drinks made from orange peel have a pH in the range of 6.77 -6.84. The resulting color values ​​indicate a significant difference in each formulation. Sensory analysis showed that the best formulation in F3 with the highest overall preference level of 3.73.